Weather Information for Garden City, 2020 - J. Elliott (Kansas Agricultural Experiment Station Research Reports, 2021)
Summary of 2020 weather for research conducted at the Garden City Kansas Agricultural Experiment Station field location.
Keywords: Garden City weather; 2020 weather; southwest Kansas weather report